Philippine contemporary ceramics a study on the emergence of ceramic practice in Philippine contemporary art from the 1970s to the present - Mendoza, Marianella Luisa
The aim of this study is to establish how ceramic practice surfaced and developed in the Philippine contemporary art scene from the 1970's to the present. It looks into the evolution of the practice from the initial role of ceramics in Philippine history from its earliest known manifestation until the period before its advent as a contemporary art form. The study establishes the context of the Philippines and the local art scene at the period of emergence, and identifies the various individuals and art institutions that played a role in this development. It likewise examines the aspects of ceramic practice that encouraged interest across generations of Philippine contemporary ceramic artists. The thesis presents how the synthesis of various factors brought about the emergence of ceramics as an art form in the Philippine contemporary art scene.